Endoscopic transorbital extradural anterior clinoidectomy: A stepwise surgical technique and case series study [SevEN-013] - Lim, Jaejoon; Sung, Kyoung Su; Yoo, Jihwan; Oh, Jiwoong; Moon, Ju Hyung (Frontiers in Oncology, 2022)
Background: Anterior clinoidectomy is an important procedure for approaching the central skull base lesions. However, anterior clinoidectomy through the endoscopic transorbital approach (ETOA) still has limitations due to technical difficulties and the structural complexity of the anterior clinoid process (ACP). Therefore, the authors designed a stepwise surgical technique of extradural anterior clinoidectomy through the ETOA. The purpose of this study was to evaluate the feasibility of this technique. Methods: Anatomical dissections were performed in 6 cadaveric specimens using a neuroendoscope and neuro-navigation system. The extradural anterior clinoidectomy through the ETOA was performed stepwise, and based on the results, this surgical technique was performed in the 7 clinical cases to evaluate its safety and efficiency. Results: Endoscopic extradural anterior clinoidectomy was successfully performed in all cadaveric specimens and patients using the proposed technique. This 5-step technique enabled detachment of the lesser wing of sphenoid bone from the ACP, safe unroofing of the optic canal, and resection of the optic strut without injuring the optic nerve and internal carotid artery. Since the sequential resection of the 3 supporting roots of the ACP was accomplished safely, anterior clinoidectomy was then successfully performed in all clinical cases. Furthermore, no complications related to the anterior clinoidectomy occurred in any clinical case. Conclusion: We designed a stepwise surgical technique that allows safe and efficient anterior clinoidectomy through the ETOA. Using this technique, extradural anterior clinoidectomy can be accomplished under direct endoscopic visualization with low morbidity. Since this technique is applicable to the central skull base surgery where anterior clinoidectomy is necessary, it expands the application of the ETOA.